High-precision cavity spectroscopy using high-frequency squeezed light - Junker, Jonas; Wilken, Dennis; Huntington, Elanor; Heurs, Michele (Optics Express, 2021)
In this article, we present a novel spectroscopy technique that improves the signal-to-shot-noise ratio without the need to increase the laser power. Detrimental effects by technical noise sources are avoided by frequency-modulation techniques (frequency up-shifting). Superimposing the signal on non-classical states of light leads to a reduced quantum noise floor. Our method reveals in a proof-of-concept experiment small signals at Hz to kHz frequencies even below the shot noise limit. Our theoretical calculations fully support our experimental findings. The proposed technique is interesting for applications such as high-precision cavity spectroscopy, e.g., for explosive trace gas detection where the specific gas might set an upper limit for the laser power employed.
CRIS-Team Scopus Importer:2023-04-20